The role of epicardial fat in pericardial diseases - Lazaros, G; Antonopoulos, A; Antoniades, C; Tousoulis, D (Springer, 2018)
PURPOSE OF REVIEW:Despite the recent advancements in diagnostic modalities and therapeutic options available, the pathophysiology of pericardial syndromes remains poorly understood. In this review article, we explore the possible links between cardiac adiposity and pericardial syndromes. RECENT FINDINGS:Over the last years, the notion of cardiac adipose tissue has radically changed, and its pivotal role in myocardial diseases has been acknowledged. Recent evidence suggests a cross-talk between epicardial fat and the heart. Imaging of epicardial and pericardial adipose tissue has an independent predictive/prognostic value in cardiovascular disease. Recent data suggests that imaging of epicardial adipose tissue may also provide prognostic information on the clinical course of patients with acute pericarditis. Evidence from clinical and translational studies suggests possible links between epicardial fat and pericardial diseases, which need to be further explored. Epicardial adipose tissue could have a role both as a prognostic biomarker in pericardial syndromes and as potential therapeutic target for pericardial diseases. The findings of future research in the field are eagerly anticipated.